Transnational German film at the end of neoliberalism : radical aesthetics, radical politics - Breger, Claudia; Landry, Olivia (Screen cultures, 2024)
"Posits a new, aesthetically and politically radical, transnational German cinema-"transnational" also in the sense of concerns with migration, the movement of capital across borders, and globalization. This book makes a bold claim that, since around 2015, a new, transnational German cinema has arisen that is aesthetically and politically radical. "Transnational" here denotes not merely international co-productions but extends to theme and form in the films' concerns with movements of people and capital across borders and with globalization. The volume analyzes key films ranging in genre and mode from dramas and comedies, including the "New German Discourse Comedy," to documentaries and installations. The essays illuminate a shift beyond neoliberal stasis and a renewed embrace of political filmmaking that confronts realities of the present. Analyzing works by a diverse array of filmmakers - including Fatih Akın, Irene von Alberti, Amel Alzakout and Khaled Abdulwahed, Forensic Architecture, Ruth Beckermann, Nils Bökamp, Susanne Heinrich, Gerd Kroske, Burhan Qurbani, Christian Petzold, Mario Pfeifer, Julian Radlmaier, Maria Speth, Tatjana Turanskyj, and Monika Treut - the contributions provide a broad yet in-depth look at contemporary German film. Through formal innovation as well as explicitly political storytelling, this cinema, the essays argue, points beyond political crises, social precarity, and the impasses of the present, sometimes with imagination and fantasy and often by embracing collectivity and resistance. Edited by Claudia Breger and Olivia Landry. Contributors: Hester Baer, Angelica Fenner, Randall Halle, Lutz Koepnick, Angelos Koutsourakis, Richard Langston, Priscilla Layne, Ervin Malakaj, Gozde Naiboglu, and Fatima Naqvi"--